Juridification of examination systems: extending state level authority over teacher assessments through regrading of national tests. Issue 5 (3rd September 2017) - Novak, Judit; Carlbaum, Sara
Abstract: Since 2009, the Swedish Government uses an 'audit' agency – the Swedish Schools Inspectorate – to monitor and assess the accuracy with which teachers grade student responses on national tests. This study explores the introduction and subsequent establishment of the Inspectorate's regrading programme as an example of political management of the tensions between competition and equity inherent in neoliberal regulatory regimes. The programme is considered a case for examining contemporary policies and discourses on fairness and government actions undertaken to resolve issues of unfair assessment and safeguard students' rights. Work of Carol Bacchi forms part of the theoretical background for the investigation of problem representations around and within the programme. The article demonstrates how discursive practices in the fields of government, audit and media have worked to frame teachers' assessments as incorrect, unfair and as jeopardizing the credibility of the grading system, thus justifying increased central control and authority over teacher assessments. As such, the regrading programme contributed to increased mistrust in teacher professionalism. A legal discourse is identified, and we argue the examination system is being juridified where the abundance of control over knowledge risks turning into a deficit of that same knowledge.